Newsreel2. New Teaching Fields for the Next Generation of Journalists - Pinto-Martinho, A.; Crespo, M.; Andrade, Wanessa; Torbó, A.; Speck, D.; Fengler, S.; Polyák, G.; Matei, A.; Radu, R.; Kreutler, M.; Sercan, E.; Popovici, M.; et al. (2021)
The pace of digital disruption forces media outlets throughout Europe to become more flexible and adaptable than ever before with regard to business models, content, and the means of distribution of that content. Consequently, many journalists constantly need to acquire new skills and thus require further education. Every few years new social networks attract new users, innovative technologies require attention, especially while there is still uncertainty about whether they will ever become mainstream. Pioneer journalists “establish new organizational figurations” (Hepp & Loosen, 2021, 591) of journalism beyond the classical news organization, transforming perceptions of journalism and the journalistic workspace. Such innovations also require journalists to work in a more interdisciplinary manner, closely cooperating with software developers, data specialists, and business developers, which further transform the journalistic professionalism and the skills journalists need to fulfil expectations from both employers and the audience. This has contributed to the evolution of “hybrid” roles and types of journalism (Splendore & Brambilla, 2021). These developments pose a challenge for journalism educators at universities, journalism schools or at institutions of further education. Adapting curricula at such a rapid pace is challenging and requires constant exchange with practitioners. At the same time, journalism schools should refrain from following every trend, and focus on the core competencies of the journalistic crafts (Bettels- Schwabbauer et al., 2018, 90). However, it is crucial to acknowledge that the “market” for young professionals in journalism is in constant transformation, and journalism educators need to consider this, in order to find a robust balance between tradition and disruption. For the second time, our project consortium sets out to explore the need for innovation in a variety of fields of journalism education. Our first EU-funded project NEWSREEL - New Skills for the Next Generation of Journalists focussed on four fields – data journalism, collaborative journalism, innovative business models and ethical challenges of the digital public sphere. Following the research stage of the NEWSREEL project (see Bettels-Schwabbauer et al., 2018), the team developed journalism and media curricula and e-learning materials. NEWSREEL2 - New Teaching Fields for the Next Generation of Journalists widens the scope with nine additional fields: i) Storytelling in social media ii) Graphic journalism iii) Improving democratic sensibility iv) Covering migration v) Foreign coverage vi) Journalism for voice-activated assistants and devices vii) AI and journalism, robot journalism and algorithms viii) Verifying and analysing fake news ix) Debunking disinformation